Knowing Differently in Systemic Intervention. (September 2015) - Rajagopalan, Raghav; Midgley, Gerald
<x xml:space="preserve">Abstract</x> This paper makes the case for extended ways of knowing in systemic intervention. It argues that the deployment of formal (even reflective) thinking and dialogue methods are inadequate, on their own, to the critical tasks of comprehending larger wholes and appreciating others' viewpoints. Theory and techniques need to go further and access other forms of knowing, held in experiential, practical or symbolic ways. This could offer a better basis to incorporate marginalized people and other phenomena that are affected by interventions but do not have a voice, such as ecosystems and future generations. Copyright © 2015 John Wiley & Sons, Ltd.